Reversal of cadmium-induced toxicity in Meretrix meretrix as determined by alleviation of oxidative damage following short-term depuration - Zhou, Jian; Cai, Huiqi; Zhong, Yuning; Zheng, Yu; Wu, Yinuo; Chang, Alan Kueichieh; Ying, Xueping (Frontiers in Marine Science, 2024)
Cadmium (Cd) is a toxic heavy metal that, when present as a pollutant in the marine environment, is readily accumulated by marine bivalves, causing oxidative stress and tissue damage. This study explored whether short-term depuration could reverse Cd2+-induced toxicity in the ovary of the clam Meretrix meretrix. Clams exposed to 3 mg·L-1 Cd2+ for three days showed increased accumulated Cd2+ in their ovaries with obvious tissue damage as shown by loose structure and some apoptotic cells compared with non-exposed clams. Increased oxidative stress in the ovarian tissue was also obvious, as revealed by increased levels of oxidative indicators such as reactive oxygen species (ROS), malondialdehyde (MDA), DNA-protein crosslinking (DPC), and protein carbonylation (PCO) and increased expression levels of genes related to oxidative stress and apoptosis, which included Bax, Bcl-2, caspase-3, HO-1, Hsp70, NQO1, Nrf2, and MT genes. When the clams were exposed to Cd2+ for three more days, the accumulated Cd2+ level in the ovary increased to more than 10-fold the level in the control clams, accompanied by more severe damage and cell death as well as oxidative stress. However, when the initial three-day Cd2+ exposure was followed by three days of depuration in Cd2+-free seawater, the Cd2+ level in the ovary was reduced by as much as 20%, accompanied by some recovery of tissue damage and reduced oxidative stress, suggesting that short-term depuration may mitigate Cd2+-induced toxicity in M. meretrix, allowing the clams to recover and potentially reducing the risk of Cd2+ exposure from consuming contaminated clams.